Determining Debris Collection Areas for the European Side of İstanbul - DEMİREL, DUYGUN FATİH; Gönül Sezer, Eylül Damla (Springer Science and Business Media Deutschland GmbH, 2025)
It is crucial to rapidly remove the debris generated after an earthquake, dispose of it in designated areas, and manage it using various methods. Especially in cities like Istanbul, which face a constant earthquake threat, it is essential to develop disaster management plans in advance. One key aspect of these plans is identifying suitable locations for debris collection after an earthquake. Studies in the literature show that different methods are used to consider multiple economic and environmental criteria for debris site selection. However, the lack of a similar scientific study for Istanbul is a significant gap. This project proposes a hybrid method that incorporates sustainable approaches to identify debris collection areas on the European Side of İstanbul. The study aims to identify potential debris sites. The selection model will be based on the multi-attribute utility theory (MAUT), considering factors like cost, environmental impact, proximity to debris areas and recycling centres, and effects on water resources and natural habitats.
Keywords: Debris Management; Multi-attribute Utility Theory; Multi-criteria Decision Making; Sustainability